Analisis Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia di Kabupaten/Kota Provinsi Bali (Metode Kointegrasi) - Muhammad Virgi Hariyanto; Putu Ayu Pramitha Purwanti (Trunojoyo University of Madura, 2020)
Bali Province has had sufficient economic growth in recent years. Decentralization that is emphasized in each region demands for each region to be independent in managing its economy. Relatively good economic growth is expected to have an effect on the Human Development Index in the area. This study aims to analyze the long-term relationship between economic growth and the Bali Province HDI. The data used are panel data on economic growth and district / city level HDI in Bali Province for the period 2004-2017. The analysis used first, Klassen Typology, secondly cointegration ,. With the stage of using the Unit Roots Test to test the stationarity of the variable. The results of the Klassen Typology show that Badung Regency, Denpasar City, and Gianyar Regency fall into the fast-growing and fast-growing regional category, Buleleng Regency falls into the fast-developing area category, Jembrana Regency and Tabanan Regency fall into the category of potential but depressed regions. Bangli Regency, Karangasem Regency, and Klungkung Regency fall into the relatively backward regional category. The results of the cointegration method show a long-term balance (cointegration) relationship between economic growth and HDI in Bali Province.